Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I cannot see how to find a way to prove that if $H$ is a subgroup of $G$ such that the product of two right cosets of $H$ is also a right coset of $H,$ then $H$ is normal in $G.$

(This is from Herstein by the way.)

Thank you.

share|improve this question
    
There might be something missing from your question. What is your definition of the product of two cosets? Isn't it always a coset? –  M Turgeon Aug 8 '12 at 22:27
    
For $a,b \in G,$ $HaHb = \{(h_1a)(h_2b) | h_1,h_2 \in H\}.$ i.e. we want to show that if for any $a,b \in G,$ we have that for some $c \in G, HaHb=Hc,$ then $H$ is normal. –  Souparna Purohit Aug 8 '12 at 22:31
    
@MTurgeon $G/H$ is a group only when $H$ is normal. If $H$ is not normal, multiplication of cosets is not well-defined. –  Code-Guru Aug 8 '12 at 22:58
    
@limac246 What have you tried? I suggest starting with the definitions of a normal subgroup and coset multiplication. –  Code-Guru Aug 8 '12 at 22:59
    
@Code-Guru I know this. My point is that the usual way to define multiplication shows that the product of two cosets is a "coset", e.g. $(aH)(bH)=(ab)H$. The point is the well-definedness; I was wondering if this is what the OP was trying to show. –  M Turgeon Aug 8 '12 at 23:15
show 2 more comments

2 Answers 2

up vote 8 down vote accepted

Hint: if $HaHa^{-1}$ and $Ha^{-1}Ha$ are right cosets they must be $H$ because they contain the identity.

(I have updated my hint to involve both $HaHa^{-1}$ and $Ha^{-1}Ha$ because $aHa^{-1}\subseteq H$ is not by itself equivalent to $aHa^{-1}=H$ when $H$ is infinite; see counterexamples here, here, here.)

share|improve this answer
    
I'm not sure how this, as it is written, answers the OP's question: we know $\,H\,$ is a subgroup and we want to show that if a product of right cosets (the pointwise product, I guess, stemming from the group operation) is again a right coset then this sbgp. is in fact normal. Now, this follows exactly from the above: $$\forall a\in G\,\forall x,y\in H\,\exists h\in H\,\,s.t.\,\,xa^{-1}ya=h\Longrightarrow a^{-1}ya=x^{-1}h\in H$$and we're done. But how the identity in $\,H\,$ helps here? –  DonAntonio Aug 9 '12 at 0:05
    
Hmmm...and still the above isn't complete (im my mind, of course) as the rightmost rightcoset doesn't have to be $\,H\,$, it could be $\,Hb\,$, say.. –  DonAntonio Aug 9 '12 at 0:07
    
@DonAntonio: this is a complete proof. If $Ha^{-1}Ha=H$, then $a^{-1}Ha=H$ and $H$ is normal. In particular, it is not necessary to assume that $HaHb=Hc$ for all pairs $(a,b)$, but only for pairs where $b=a^{-1}$. The reason we need the identity for $c$ is so that you get your $xa^{-1}ya = hc$ to actually be in $H$. If $c$ were not in $H$, then we would not conclude $H$ is normal, but rather reach a contradiction. –  Jack Schmidt Aug 9 '12 at 0:17
    
Exactly my point, @JackSchmidt ! How can we know a priori that $\,Ha^{-1}Ha=H\,$ ? This is the whole point. Of course, we can argue that since $\,Ha^{-1}Ha=Hc\,$ then for all $\,x,y\in H\,$ we have that $\,xa^{-1}ya=hc\,$ , in particular if we choose $\,y=1\in H\Longrightarrow xa^{-1}a=x=hc\in G\Longleftrightarrow c=1\,$ as we know right cosets are a partition of $\,G\,$...hmm, perhaps this is what anon meant...yes, I think it is and I didn't see clearly his hint though I knew that taking $\,Ha\,,\,Ha^{-1}\,$ is the way to prove the claim...damn, what a nice though aethereal hint! +1 –  DonAntonio Aug 9 '12 at 2:07
    
@DonAntonio It is a fact that the only coset of a given subgroup containing the identity is the subgroup itself. Another fact is that for any subset $S\subseteq G$ and subgroup $H\le G$, we have $SH\subseteq H\iff S\subseteq H$. (Same for $HS$.) In my opinion these should be standard exercises. –  anon Aug 9 '12 at 2:23
show 3 more comments

A (not quite as) short alternate proof:

If $HaHb=Hc$ then $HaHb=Hab$. @anon's short proof chooses $b=a^{-1}$, but you can also choose $b=1$, since $$HaH = Ha \iff 1aH \subseteq Ha$$

Of course to get equality, we also have to use $$Ha^{-1}H =Ha^{-1} \iff a^{-1} H \subseteq Ha^{-1} \iff Ha \subseteq aH $$


In general, $HaHb=Hab \iff aHb \subseteq Hab$, so if we want $aH=Ha$ we choose $b=1$ and if we want $aHa^{-1}= H$ we choose $b=a^{-1}$. If groups are finite, we don't even have to pay attention to $\subseteq$ versus $=$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.